(untitled) - Rabun, J. Stanley (New York, 2000)
The book offers the most complete, detailed, and authentics data available on the materials, calculation methods, and design techniques used by architects and engineers of the nineteenth and early twentieth centuries. It provides today's building professionals with information needed to analyze, modify, and certify historic buildings for modern use.
Keywords: Historic building,Historic buildings,Structural analysis ( engineering ); Remodeling for other use,Honservation and restoration